Modeling demand for Islamic microfinance using partial least squares approach: evidence from Malaysia - Mohd Thas Thaker, Mohamed Asmy; Kassim, Salina; Che Mohd Salleh, Marhanum; Othman, Nadhrah; Kassim, Siti Nadhirah (2017)
The ability to access capital is highly critical in ensuring the financial sustainability of microfinance clients. In lieu of this, it becomes important to identify factors that are significant in determining the demand factors for microfinance among the clients in order to ensure that microfinance can be effectively channelled to clients. This study aims to identify significant factors determining the demand for Islamic microfinance among women micro-entrepreneurs in Malaysia. A total of 402 samples are being considered with data collected using survey questionnaire covering various centers of Amanah Ikhtiar Malaysia in Selangor. A novel aspect of this study lies on the investigation method adopted - the Partial Least Squares approach, which is being applied on potential demand factors, namely the 4As factors (Affordability, Accessibility, Adequacy and Awareness). Findings of this study provide important inputs on the critical factors to be considered in the demand for microfinance among the women micro-entrepreneurs. Microfinance providers should consider these demand factors in further refining their products and services to enhance the participation of women in microenterprises in Malaysia.